Analisis Pembangunan Kantor Camat Lalabata Kabupaten Soppeng - Ulfinawasari Ulfinawasari (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This study aimed to determine analysis of development sub office Lalabata Soppeng regency as well as the factors that influenced them. to achieve those goals, the type of research is descriptive analysis. Data collecting technique was conducted through observation, interview, and document by using descriptive-qualitative analysis. Based on the results of this research, it is known that the management of the construction sub office Lalabata Soppeng regency haven't optimal. This is apparent from the cessation of the construction in 73% of the physical building. As for the factors that influence the development sub office Lalabata Soppeng regency includes Supporting and inhibiting factors. Supporting factors is desire to create a more representative office, Position of strategic area, and There is a plan to make a Green open space (RTH) in the old location (Jl Attang Benteng) and inhibiting factors development is, The location of the sub new office is problematic and the contractor handling the project is considered negligent and not ready to handle the development